Quasi-static compressive behavior and stability analysis of cellular thin-walled beams - TIAN XinYu; DENG QingTian; LI XinBo; WANG GuoSheng; SONG XueLi (Jixie qiangdu)
The mechanical behavior and stability of thin-walled I-beams with honeycombs, concave and elliptic cellular under quasi-static uniaxial compression were studied by experiments and the finite element simulation. By comparing results of experiments and the finite element simulation, the reliability of the finite element simulation was verified. Based on experimental results and finite element simulation results, the maximum bearing capacity, elastic modulus and failure mechanism of thin-walled I-beams with honeycombs were analyzed, and the influence law of the cell type on the compression instability of thin-walled I-beam with honeycombs was obtained. The results show that the larger the distance from the hole to the flange, the better the stability of the structure. The buckling position of thin-walled I-beams with honeycombs with good stability appears between the two holes, and the concave structure has better stability than the honeycomb and elliptical structure.